Smarandache Curves In Terms of Sabban Frame of Fixed Pole Curve - Süleyman Şenyurt; Abdussamet Çalişkan (Boletim da Sociedade Paranaense de Matemática, 2016)
In this paper, we study the special Smarandache curve interms of Sabban frame of Fixed Pole curve and we give some characterization of Smarandache curves. Besides, we illustrate examples of our results.